Kedudukan Pengadilan Tinggi Tata Usaha Negara sebagai Pengadilan Tingkat Pertama (Jo. Pasal 51 ayat 3 UU 5/1986) Pasca Berlakunya Undang-Undang Nomor 30 Tahun 2014 tentang Adminitrasi Pemerintahan - Irvan Mawardi (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2019)
The Political Law of Act Number 30 of 2014 on Government Administration regulates do administrative effort must be taken before sues to administrative court. According to Article 76 paragraph 3 the Administrative Court has the authority to examine and adjudicate state administrative disputes after being taken by the Administrative Efforts. But on the other Act Number 05 of 1986 on Administrative Court concerning Article 48 jo. Article 51 Paragraph (3) also authorizes the High Administrative Court as the first degree court to examine and adjudicate on administrative decision that have been resolved through Administrative Efforts. This article try to analyze First, the pattern of administrative dispute resolution in the Administrative Court after ratification of Act Number 30 of 2014 on Government Administration. Second, the position and authority of the High AdministrativeCourt as the first degree court after ratification of Act Number 30 of 2014 on Government Administration?